BUNUH DIRI “ULAH PATI” DALAM SUSASTRA HINDU: Kajian Psikologi Agama - Sura Adnyana, Eka (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Bali ranks third with the most suicide cases in Indonesia with 638 cases, following Central Java and East Java. Suicide or often called